PENINGKATAN KUALITAS LAYANAN UNTUK KEPUASAN PELANGGAN HOTEL - hengki mangiring parulian simarmata; Doris Yolanda Saragih; Nora Januarti Panjaitan (Jurnal Ekonomi dan Bisnis (EK&BI), 2018)
The rapid development of hotel business in Pematangsiantar be an opportunity as well as challenges that must be faced by Sapadia Hotel. As a company which engaged in services, service quality becomes the key factor of success in the competition. The objective of the study is to find out the influence of service quality toward customer satisfaction at Pematangsiantar Sapadia hotel. The data collection method i is by using questionnaire and observation method, the sample of the research is 100 people by using random sampling. The dimensions to measure services namely assurance, tangibles, reliability, responsiveness, and emphaty. The data were tested with validity and reliability tests and processed with SPSS and the data analysis method which is used namely linear regression test method. The findings indicate that there are a positive and significant relationship between service quality and customer satisfaction by using R Square 58, 9% while the rest 41,1% influenced by other factors not examined in this study. For further research development can be used using other variables such as brand and loyalty.